Modelo de gestión social para la ejecución de las actividades sociales de la COAC la benéfica LTDA del cantón el Carmen - Pinto Soledispa, Jair Alexander (2019)
The objective of designing a Social Management Model for the execution of the social activities of the COAC The Charity of the El Carmen canton, was carried out in three methodological phases: define the current situation in the social sphere, develop the components of the proposal and establish the guidelines for its application. In the first phase, interviews with the managers of the cooperative were used to know the social knowledge of the administrative staff in the COAC. In the second phase, the components of the Social Management Model were developed through an adequate selection of them, with a comparative analysis for the structure of the model. In the last phase, the guidelines for the application of the model were established describing the deliverables of each of the stages of the Social Management Model with a systematic and process approach, ending with the application of the Delphi Method for the validation of the Social Management Model. Qualitative, field, bibliographic and descriptive research, as well as deductive, inductive, analytical and comparative analysis methods were applied for the execution of the research. Techniques such as interviewing and consulting an expert or Delphi method. Concluding that social management in credit unions today is a matter of legal requirement, but of great internal ignorance.